Treatment outcome with a second generation combination chemotherapeutic regimen m-BACOD and with a standard regimen chop for advance diffuse non-Hodgkin's lymphoma in elderly patients (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1841 JAFMC Bangladesh Vol.4(2) 2008 27-32